Akuntabilitas Organisasi Mahasiswa Akuntansi - Novrys Suhardianto; Hendriyat Surgandhi (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2016)
The aim of this research is to respond towards the issues about accountability practices in the Himpunan Mahasiswa Akuntansi (HMA) as an Accounting Students Association and the rationale behind carrying out the practice of its accountability mechanism. The subject of this research are the HMA’s members as well as the stakeholders. The object of this research is accountability practice held by the HMA in the period of 2012-2014. A series of data is collected through documentation and indepth interview to managers and faculty members. The results of the analysis show that the HMA helds its accountability in order to meet the terms specified by the officials which is above the HMA itself, such the faculty and university. For the management and members of the HMA, a concrete manifestation of behaviour and actions is a form of accountability. They assume that all forms of activities and the use of funds in the HMA conducted based on good faith and good behaviours, although sometime they use fake evidences to record the transactions. Abstrak Tujuan penelitian ini adalah untuk menjawab isu praktik akuntabilitas di organisasi Himpunan Mahasiswa Akuntansi (HMA) dan alasan di balik praktik akuntabilitasnya. Subyek penelitian adalah anggota dan pemangku kepentingan HMA sedangkan obyek penelitian adalah praktik akuntabilitas HMA selama 2012-2014. Data diperoleh melalui dokumentasi dan wawancara terhadap pengurus HMA dan para dosen. Hasil analisis menunjukkan bahwa HMA menyelanggarakan akuntabilitas untuk memenuhi persyaratan lembaga di atas HMA, yaitu fakultas dan universitas. Bagi pengurus dan anggota HMA, manifestasi nyata berupa perilaku dan tindakan adalah bentuk dari akuntabilitas. Asumsi mereka adalah bentuk aktivitas dan penggunaan dana dilakukan berdasar kepercayaan dan sikap yang baik meskipun terkadang mereka menggunakan bukti palsu untuk mencatat transaksi